A rail corrugation measurement method based on data splicing. (May 2020) - Teng, Yun; Liu, Hongli; Liu, Jianwei; Wang, Chao; Ma, Ziji
Highlights: A novel rail corrugation measurement system by using 2D laser displacement sensors is proposed. The rail corrugation is effectively restored by the method of coarse-to-refine data splicing. The sensor deviation and pitching vibration calibrating are achieved via a simple searching method. Achieving accurate splicing via the MPGA-based refine splicing method. The proposed measurement system owns high accuracy in measuring the waveband of rail corrugation varied from 10 mm to 1 m. Abstract: Rail corrugation dynamic measurement techniques are essential to guide rail maintenance and ensuring the safety of railway transportation. However, the effective measuring wavebands covered by traditional techniques are limited. Hence, this paper constructs a novel measurement system by using 2D laser displacement sensors for accurate measuring rail corrugation (2D-RCM). At first, original discontinuous data of rail irregularities are sampled by 2D sensors, and then the accurate restoring of rail corrugation is completed by the coarse-to-refine data splicing method. Coarse splicing mainly extracts and calibrates the data of overlapping measurement area. The refine splicing is achieved by rigid transformation and multiple population genetic algorithm. The validity and repeatability of the 2D-RCM is tested by extensive experiments. The experimental results demonstrate that it owns high-precision on measuring the wavebands of corrugation varied from 10 mm to 1 m, and robust to deviations of 2D sensors and pitching vibrations of the 2D-RCM system.